The Role Of Green Marketing In Purchasing Interest In Products - Sutrisno K.Djawa; La Saudin (International Forum of Researchers and Lecturers, 2022)
The purpose of this study is to assess the impact of different components of the green marketing mix. Specifically, the impact of green product, green pricing, green location, and green advertising on Armour Coffee purchase intentions in Maros Regency. The data utilised in this study was collected from 63 customers who had previously made purchases at the Armour Coffee location in Maros and was rigorously tested for validity, reliability, and classical assumptions. Data was collected via purposive sampling, and the results were analysed using multiple linear regression aided by the Statistical Package for Social Sciences (SPSS). Three of the five hypotheses analysed have empirical evidence to support them. Empirical results reveal that eco-friendly product and eco-friendly location qualities are favourably connected with purchase intention, whereas no significant influence is detected in regard to eco-friendly pricing and eco-promotions.